Thankful grateful blessed - Phitidis, Kimon (School of Languages and Literatures, 2025)
Kimon Phitidis first visited Gansbaai Academia –a high school in the remote town of Gansbaai in the Western Cape – in 2018 to interview Wilton Phillips. He was one of sixteen teachers profiled in Phitidis' book, Where Light Shines Through: tales of can-do teachers in South Africa's no-fee public schools. The school immediately captured his imagination. Firstly there was its name. Not Gansbaai High School. But Gansbaai Academia. It suggested an aspiration to be more. There was something going on there – something unusual – that he was drawn to understand. He spent two and a half years visiting the school and its alumni looking for answers. This is the story of what he discovered. It is a quest to understand how a state-sponsored pocket of care might come about in a country characterised by government neglect. It is a quest to understand how relationships of trust and belief formed at school drive the prospects of young people after school. And it is a quest to understand – if the magic that he sensed there is real – if it can be sustained in a crumbling public service environment and against the demands of a small town's growing population. This is an anthology of loosely connected stories about five boys who attended that school in the first few years after it opened. It is the story of their relationships with teachers and with each other and how those relationships fuelled their belief that there was a worthwhile life for them beyond the school gates; if they could smash through the many obstacles on their way to grab it. It is a story of their lives after school and their quest to realise a promise that should be made to every South African child: that, despite the many failings of our society and one of the highest youth unemployment rates in the world, each child has the right to a tertiary education and a life of dignified work. Those promises are inherent to our Constitution. He spoke to many people along the way, and this work includes their voices as they tell of five men who graduated from Gansbaai Academia and what became of them when they left.